Urgensi Pendidikan Agama Islam dalam Upaya Mengatasi Dekadensi Etika Komunikasi Siswa dengan Guru - Zhunnun Qothrunnada Annisa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research applies a qualitative method with data accumulation in the form of observations, interviews, and documentation as support. The role of Islamic religious education is very important in shaping the character of students. It is necessary to make efforts to overcome moral decadence, including making good adaptations in the school environment and participating in other positive activities. These habits are expected to be embedded in the soul and mind of students, and can be part of daily behavior. Efforts to overcome the decadence of student communication ethics must have very important supporting factors to be able to facilitate the implementation process, there are also inhibiting factors that are considered to hinder the implementation process. Several studies and studies on how to overcome the decadence of student communication ethics have been carried out a lot, such as character building, group guidance, counseling on polite speech. There are many studies that have been conducted, very few have examined and researched the importance of Islamic religious education for students in an effort to overcome the ethical decadence of student communication with teachers, therefore this research is considered unique by researchers. SMP Labschool Unesa 1 Surabaya considers that Islamic religious education is very important to build students' morals and character. The school seeks a way to overcome the decadence of student communication ethics by familiarizing students through religious programs that have been formed by the school. These efforts certainly have supporting and inhibiting factors in them.